Factors Associated With Concussion Nondisclosure in Collegiate Student-Athletes - Anderson, Morgan (J Athl Train, 2021)
CONTEXT: Mandated concussion education has aimed to improve student-athlete knowledge; however, some collegiate student-athletes continue to not disclose concussion. Concussion knowledge may not be the only factor influencing reporting, as student-athlete sex, sport, and pressure from external stakeholders (eg, coaches, teammates, fans, parents or family) have all been documented as influencing collegiate concussion-reporting behavior. OBJECTIVE: To examine factors associated with concussion nondisclosure in collegiate student-athletes. DESIGN: Cross-sectional study. SETTING: Four National Collegiate Athletic Association Division I and two Division II universities. PATIENTS OR OTHER PARTICIPANTS: A total of 1125 collegiate student-athletes completed the survey, and 741 provided viable responses and were included for data analysis. MAIN OUTCOME MEASURE(S): We used a 10- to 15-minute electronic or paper-and-pencil survey that asked about personal and sport demographics, diagnosed concussions and nondisclosed concussion history, concussion knowledge, and level of agreement regarding pressure to play after a head impact experienced during collegiate sport participation. Significant univariable factors were entered into a multivariable logistic regression analysis. RESULTS: Sex (P = .005), sport-risk type (P < .001), diagnosed concussion history (P < .001), concussion knowledge (P = .017), and pressure from coaches (P < .001), teammates (P < .001), fans (P = .024), and parents or family (P = .003) were factors associated with concussion nondisclosure in individual univariable logistic regressions. After we conducted multivariable analyses, male sex (P = .001), high concussion-risk sport participation (P = .048), diagnosed concussion history (P < .001), increased concussion knowledge (P = .013), and experiencing pressure from coaches to continue playing after sustaining a hit to the head (P = .002) were factors associated with concussion nondisclosure in collegiate student-athletes. CONCLUSIONS: Our results suggest that concussion-education programs should go beyond the identification of signs and symptoms to include the dangers of continuing to play, long-term consequences, and transparency about concussion protocols. Comprehensive concussion-education programs should involve coaches and athletes to improve the reporting culture.